Isolation and characterization of Keratinibaculum paraultunense gen. nov., sp. nov., a novel thermophilic, anaerobic bacterium with keratinolytic activity. Issue 1 (27th June 2013) - Huang, Yan; Sun, Yingjie; Ma, Shichun; Chen, Lu; Zhang, Hui; Deng, Yu
Abstract A novel thermophilic, anaerobic, keratinolytic bacterium designated KD‐1 was isolated from grassy marshland. Strain KD‐1 was a spore‐forming rod with a Gram‐positive type cell wall, but stained Gram‐negative. The temperature, pH, and NaCl concentration range necessary for growth was 30–65 °C (optimum 55 °C), 6.0–10.5 (optimum 8.0–8.5), and 0–6% (optimum 0.2%) (w/v), respectively. Strain KD‐1 possessed extracellular keratinase, and the optimum activity of the crude enzyme was pH 8.5 and 70 °C. The enzyme was identified as a thermostable serine‐type protease. The strain was sensitive to rifampin, chloramphenicol, kanamycin, and tetracycline and was resistant to erythromycin, neomycin, penicillin, and streptomycin. The main cellular fatty acid was predominantly C15:0 iso (64%), and the G+C content was 28 mol%. Morphological and physiological characterization, together with phylogenetic analysis based on 16S rRNA gene sequencing identified KD‐1 as a new species of a novel genus of Clostridiaceae with 95.3%, 93.8% 16S rRNA gene sequence similarity to Clostridium ultunense BST (DSM 10521T) and Tepidimicrobium xylanilyticum PML14T (= JCM 15035T), respectively. We propose the name Keratinibaculum paraultunense gen. nov., sp. nov., with KD‐1 (=JCM 18769T =DSM 26752T) as the type strain.